Necessity as the mother of invention: monetary policy after the crisis - Blinder, Alan S.; Ehrmann, Michael; de Haan, Jakob; Jansen, David-Jan (Frankfurt am Main, 2017)
"We ask whether recent changes in monetary policy due to the financial crisis will be temporary or permanent. We present evidence from two surveys—one of central bank governors, the other of academic specialists. We find that central banks in crisis countries are more likely to have resorted to new policies, to have had discussions about mandates, and to have communicated more. But the thinking has changed more broadly—for instance, central banks in non-crisis countries also report having implemented macro-prudential measures. Overall, we expect central banks in the future to have broader mandates, use macro-prudential tools more widely, and communicate more actively than before the crisis. While there is no consensus yet about the usefulness of unconventional monetary policies, we expect most of them will remain in central banks’ toolkits, as governors who gain experience with a particular tool are more likely to assess that tool positively."